Teacher Trainees’ Attitude And Motivation Towards Using The Internet As Resource For ESL Classroom - Abdul Razak, Noor Zainab; Sanmugam, Shamini (2010)
The purpose of this is to investigate teacher trainees’ attitude and motivation towards using the Internet as resource for the ESL classroom. The respondents in this study are 40 TESL teacher trainees in third and fourth year from Faculty of Education. The methodology used in this study is a set of questionnaire. The data in this study have been analyzed using SPSS 12.0 software (Statical Packages for Social Science) and presented in the form of frequency and percentage. The findings of this study explain that most of the teacher trainees have a positive attitude towards the use of the Internet for the ESL classroom. Through this study, it could be concluded that the use of the Internet for the ESL classroom should be encouraged because it helps to motivate teacher trainees and generate a positive attitude towards English language learning.